Transcriptome-wide m6A methylation in natural yellow leaf of Catalpa fargesii - Zhang, Yu; Wang, Junhui; Ma, Wenjun; Lu, Nan; Fu, Pengyue; Yang, Yingying; Zhao, Linjiao; Hu, Jiwen; Qu, Guanzheng; Wang, Nan (Frontiers in Plant Science, 2023)
N6-methyladenosine (m6A) is the most abundant internal modification in eukaryotic messenger RNA, and involved in various biological processes in plants. However, the distribution features and functions of mRNA m6A methylation have been poorly explored in woody perennial plants. In this study, a new natural variety with yellow-green leaves, named Maiyuanjinqiu, was screened from the seedlings of Catalpa fargesii. Based on the preliminary experiment, the m6A methylation levels in the leaves of Maiyuanjinqiu were significantly higher than those in C. fargesii. Furthermore, a parallel analysis of m6A-seq and RNA-seq was carried out in different leaf color sectors. The result showed that m6A modification were mostly identified around the 3’-untranslated regions (3’-UTR), which was slightly negatively correlated with the mRNA abundance. KEGG and GO analyses showed that m6A methylation genes were associated with photosynthesis, pigments biosynthesis and metabolism, oxidation-reduction and response to stress, etc. The overall increase of m6A methylation levels in yellow-green leaves might be associated with the decreased the expression of RNA demethylase gene CfALKBH5. The silencing of CfALKBH5 caused a chlorotic phenotype and increased m6A methylation level, which further confirmed our hypothesis. Our results suggested that mRNA m6A methylation could be considered as a vital epigenomic mark and contribute to the natural variations in plants.